Thoracoscopic Resection of a Foregut Duplication Cyst with the Use of a 5-mm Stapling Device in an Infant—A Case Report - Da Col, Marc; Regamey, Nicolas; Szavay, Philipp O. (European Journal of Pediatric Surgery Reports, 2022)
Esophageal foregut duplication cysts are a rare congenital anomaly predominantly diagnosed in children. With possible growth foregut duplication cysts may cause compression on thoracic or mediastinal structures, respectively. Due to the presence of ectopic gastric mucosa and its potential malignant alteration resection of foregut duplication cysts is recommended. More recently, the use of a thoracoscopic approach for resection has shown to be an advantageous alternative to a conventional open approach. A case of a complete thoracoscopic resection of an esophageal foregut duplication cyst using a 5-mm stapling device is presented.
Keywords: foregut duplication cyst; thoracoscopy; stapling device; VATS; pediatric